Defying easy explanations—the case of Pennington v Waine 18 years on. Issue 5 (1st May 2020) - Sutherland, Sean
Abstract: The case of Pennington v Waine has been subject to extensive scholarly attention. Many have sought to fit the case into established categories, such as proprietary estoppel or the rule in Re Rose . This article will argue that the case cannot be explained with these easy explanations. Instead it marks a radical shift in the law and is indicative of an equity that is "on the move".